The Melanau folklore: an analysis of moral values - Hishamuddin Siri; Hafizan Mohamad Naim; Abdul Walid Ali (Penerbit Universiti Kebangsaan Malaysia, 2024)
Melanau folklore, abundant with intricate narratives and moral lessons, serves as an essential vehicle for cultural transmission. This paper seeks to scrutinize the representation of moral values within Melanau folklore, specifically looking through its oral narratives through qualitative literary research. Drawing on the thematic analysis of 24 short stories derived from Morris's monograph, this paper identified four principal themes of moral values: Personal Development and Growth, Social and Cultural Values, Interactions with the Supernatural, and Environmental Stewardship. These moral values, deeply embedded in Melanau's worldview, are paramount to the community's understanding and interaction with their environment. Intriguingly, our analysis suggests that the inherent moral values of the Melanau are often intertwined with concepts related to the spirit world, indicating the pivotal role of supernatural elements in shaping the community's ethical landscape. This study highlights the rich moral fabric of Melanau narratives, elucidating their cultural identity and the broader context of their relationship with the supernatural world.